2017
DOI: 10.1002/2016jb013798
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical derivation of flow laws for quartz dislocation creep: Comparisons with experimental creep data and extrapolation to natural conditions using water fugacity corrections

Abstract: We theoretically derived flow laws for quartz dislocation creep using climb‐controlled dislocation creep models and compared them with available laboratory data for quartz plastic deformation. We assumed volume diffusion of oxygen‐bearing species along different crystallographic axes (//c, ⊥R, and ⊥c) of α‐quartz and β‐quartz, and pipe diffusion of H2O, to be the elementary processes of dislocation climb. The relationships between differential stress (σ) and strain rate ( trueε˙) are written as trueε˙∝σ3Dv an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 80 publications
0
33
1
Order By: Relevance
“… Note . In a theory by Fukuda and Shimizu (), μ is the shear modulus of quartz (42 × 10 3 MPa), b is the burgers vector (5 × 10 −10 m), k is the Boltzmann constant (1.381 × 10 −23 J/K), D 0 is the preexponential factor for diffusion of oxygen‐bearing species parallel to the c axis in α quartz by Farver and Yund () taking into account the effect of water fugacity in Fukuda and Shimizu () (5.8 × 10 −7 m 2 /s MPa − r with r = 1), and Q is its activation energy. GSI = grain‐size‐insensitive creep; GSS = grain‐size‐sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Note . In a theory by Fukuda and Shimizu (), μ is the shear modulus of quartz (42 × 10 3 MPa), b is the burgers vector (5 × 10 −10 m), k is the Boltzmann constant (1.381 × 10 −23 J/K), D 0 is the preexponential factor for diffusion of oxygen‐bearing species parallel to the c axis in α quartz by Farver and Yund () taking into account the effect of water fugacity in Fukuda and Shimizu () (5.8 × 10 −7 m 2 /s MPa − r with r = 1), and Q is its activation energy. GSI = grain‐size‐insensitive creep; GSS = grain‐size‐sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Quartz grain size paleopiezometers (shown by dashed lines) by St06 + H&K10 (Stipp et al, , with the stress correction in Holyoke and Kronenberg, ) for regime 1 [steeper in (a)] and regimes 2 and 3 [gentler in (a) and this is shown only in (b) for three grain sizes for simplicity], Sh08 (Shimizu, ). Flow laws by L&P92 (Luan & Paterson, ); L&P92 + F&S17 (Luan & Paterson, , redetermined by Fukuda & Shimizu, ); R&B04a, b (Rutter & Brodie, , ); H01 + H&K13 (Hirth et al, , revised by Holyoke & Kronenberg, ); and F&S17 (Fukuda & Shimizu, ; Theory).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present experiments found that MgSiO 3 bridgmanite is the liquidus phase of melts with a wider range of SiO 2 /(MgO + SiO 2 ) ratios than previously predicted by ab initio calculations and thermodynamic modeling. (Fukuda & Shimizu, 2017); while SiO 2 stishovite is more viscous than MgSiO 3 bridgmanite (Xu et al, 2017), quartz usually includes water and is thus a weak phase.…”
Section: Geophysical Implicationsmentioning
confidence: 99%